Phanerozoic Morphotectonic Evolution of the Zimbabwe Craton: Unexpected Outcomes From a Multiple Low‐Temperature Thermochronology Study. Issue 10 (17th October 2017) - Mackintosh, Vhairi; Kohn, Barry; Gleadow, Andrew; Tian, Yuntao
Abstract: The fragmentary Phanerozoic geological record of the anomalously elevated Zimbabwe Craton makes reconstructing its history difficult using conventional field methods. Here we constrain the cryptic Phanerozoic evolution of the Zimbabwe Craton using a spatially extensive apatite (U‐Th‐Sm)/He (AHe), apatite fission track (AFT), and zircon (U‐Th)/He (ZHe) data set. Joint thermal history modeling reveals that the region experienced two cooling episodes inferred to be the denudational response to surface uplift. The first and most significant protracted denudation period was triggered by stress transmission from the adjacent ~750–500 Ma Pan‐African orogenesis during the amalgamation of Gondwana. The spatial extent of this rejuvenation signature, encompassing the current broad topographic high, could indicate the possible longevity of an ancient topographic feature. The ZHe data reveal a second, minor denudation phase which began in the Paleogene and removed a kilometer‐scale Karoo cover from the craton. Within our data set, the majority of ZHe ages are younger than their corresponding AHe and AFT ages, even at relatively low eU. This unexpectedly recurrent age "inversion" suggests that in certain environments, moderately, as well as extremely, damaged zircons have the potential to act as ultra‐low‐temperature thermochronometers. Thermal history modeling results reveal that the zircon radiation damage accumulation and annealing model (ZRDAAM) frequently overpredicts the ZHe age. However, the opposite is true for extremely damaged zircons where the ZHe and AHe data are also seemingly incompatible. This suggests that modification of the ZRDAAM may be required for moderate to extreme damage levels. Key Points: Zimbabwe Craton experienced uplift and denudation following stress transmission from Pan‐African orogenesis during Gondwana amalgamation First zircon He data reveal removal of variable kilometer‐scale Karoo sedimentary cratonic cover began in the Paleogene Zircon He ages younger than apatite He or fission track ages suggest that moderate eU zircons can be ultra‐low‐temperature thermochronometers